Five minds for the future - Gardner, Howard, 1943- (Leadership for the common good., 2007)
Argues that the future requires individuals to learn and think in different ways, and defines the cognitive abilities that an individual must master, including the ability to integrate ideas from different disciplines and an appreciation for differences among humans.